Przykład dziejowej roli arcybiskupa Josyfa Slipyja (1892-1984) - Moskałyk, Jarosław (Poznańskie Studia Teologiczne, 2012)
The presented here brief overview of the historical role of the spiritual leader of the Greek Catholic Church of the 20th century Josyf Slipyj is primarily aimed at paying him proper tribute on the 120th anniversary of his birth, but it is also an attempt to look at his person in a broader historical and ecclesial context. Despite his enormous contribution to a comprehensive development of the Eastern Catholic Church of the Kiev tradition and the empowerment of Eastern Catholic communities, the person of Slipyj is still insufficiently recognized both in his own country and in the world. In addition, especially in the Orthodox environment he sometimes happens to be seen as a staunch or even fanatical defender of the Catholic vision of the universality of the Church, which today is largely at odds with the principle of an open ecumenical activity. However, this is an isolated position, which has no grounds in the actual state of matters as can be concluded even from this article.